Polymicrobial Osteomyelitis in a Patient With Isolation of Trueperella bernardiae: A Case Report and Literature Review - Marco Antonio Delaye-Martínez; Edgar Samuel Vanegas-Rodríguez; Braulio Mendez-Sotelo; María de Lourdes García-Hernández; Claudia Adriana Colín-Castro; Rafael Franco-Cendejas; Luis Esaú López-Jácome (Case Reports in Infectious Diseases)
Conclusions: Trueperella bernardiae represents an emerging bacterium that can be isolated in various clinical presentations. On osteoarticular infections, the presence of comorbidities, mobility limitations, and a history of multiple antibiotic treatments may be determinant. Their isolation as part of polymicrobial infections highlights relevant interspecies interactions. Research is still lacking in determining standardized methodologies for susceptibility testing and specific clinical breakpoints to guide clinical decisions.